PENGARUH PENGGUNAAN ALAT TANGKAP RAWAI DASAR (BOTTOM LONG LINE) PADA KEDALAMAN DAN WAKTU YANG BERBEDA TERHADAP HASIL TANGKAPAN DIPERAIRAN TELUK AWANG: The Effect Of Using Bottom Long Line Gear At Different Depths And Times On The Catch Results In The Waters Of Teluk Awang - Masturyadi, Masturyadi; Rizal, Lalu Samsul; Furkan, Al (Yayasan Al-Amin Qalbu, 2025)
The purpose of this study was to determine the most effective water depth and the right time and the types of fish caught using bottom long line fishing gear (Bottom Long Line). This study was conducted in the waters of Teluk Awang, Central Lombok Regency. The method used in this study is the